Model system study of recycled polyethylene terephtalate and polyprpylene blends - Cardfelt, Anders (My University, 2015)
Recycling of polymers becomes an increasingly important issue because of the environmental impact of petroleum-based polymer production. Legislative motivation also pushes for polymer recycling with the End-of-Life-Vehicles (ELV) directive dictated by the European Union requiring that a minimum of 85 wt% of vehicles are materials recycled. This creates a need to recycle interior parts from cars for example compression molded panels that consist of several polymers, such as polypropylene (PP) and polyethylene terephthalate (PET). Recycling of polymer blends can be a problematic process due to phase incompatibility. The compatibility of PP and PET, can be increased by adding compatibilizing agents that lower the interfacial tension. Adhesion between the phases can be increased as well resulting in a stronger and more elastic material. During processing of PET, degradation by hydrolysis results in loss in molecular weight. Chain extenders can be added to counteract this effect and thereby strengthening the material. The aim of the master’s thesis work was to investigate a system model for processing and upgrading recycled PP and PET fibers that can be industrially applicable. This was done by evaluating virgin PP pellets and PET fiber blends. The upgrading was performed by adding compatibilizing agents and chain extenders to the PP and PET blends. The study focused on maximizing the mechanical properties for the blends produced. The effect of compatibilizers, chain extenders and glass fiber was analyzed with mechanical analysis, differential scanning calorimetry, fourier transform infrared spectroscopy and scanning electron microscopy. The results showed that for maleic anhydride grafted PP compatibilized blends the yield strength was increased and combined with epoxy or oxazoline chain extenders even higher yield strength was observed. This was achieved by a very good dispersion of PET the phase in the PP matrix. High shear mixing in a regular twin screw extruder showed that the concept is industrially applicable.
Keywords: Materialvetenskap; Hållbar utveckling; Kemiteknik; Materialteknik; Materials Science; Sustainable Development; Chemical Engineering; Materials Engineering